Análisis de la degradación de los componentes pasivos de un transformador de potencia de 10 MVA, con el fin de prolongar su vida útil, considerando su impacto al medio ambiente. - Loaiza Vera, Segundo Leonidas (2019)
In the present work a restrictive interpretation of the use and costs associated with the repair activities of a Power transformer is contemplated, based on statistical tables, infograms, histograms and physical-chemical reports of the passive components of a Power transformer, as well as methods and strategies to minimize risks to the environment, for which the corresponding information based on a transformer of Brazilian origin with 10 MVA of power that works in a substation connected to a 69 KV feeder has been raised. The results will present an analysis that will allow making objective decisions about the optimization of spending in terms of preventive and predictive maintenance plans, presented in conjunction with an adequate protocol with quantitative analysis and common risks to equipment, people and the environment. , the moment in which the maintenance activity is linked to repair technologies and cost validation in power transformers, high value assets within the Ecuadorian electrical distribution circuit that comply with national and international regulations. The results concluded that the useful life of a power transformer is related to the tracking of its chargeability and the respective predictive analyzes, taken together with preventive maintenance plans whose protocol revision is suggested to be audited every two years, which would guarantee an increase The useful life and prevent essential damage in a Power transformer.